Fe2 Dimers for Non‐Polar Diatomic O2 Electroreduction. Issue 15 (22nd June 2022) - Fan, Ruxue; Wang, Haiyan; Zheng, Xiaozhong; Chen, Jiadong; Ou, Yang; Wang, Yong; Mao, Shanjun
Abstract: Non‐polar diatomic molecule activation is of great significance for catalysis. Despite the high atomic efficiency, the catalytic performance of single‐atom catalysts is limited by insufficient receiving sites for diatomic molecule adsorption. Here, Fe2 dimers were successfully synthesized through precisely regulating the metal loading on metal‐organic frameworks. The unique role of metal dimers in activating diatomic O2 molecules was explored. In alkaline electrolytes, the specific oxygen reduction reaction activity of Fe2 dimers was 7 times higher than that of Fe1 counterparts. The hydrogen atom transfer probes indicated a different activation mode for O2 on Fe1 and Fe2 dimers, respectively. Theoretical calculation results revealed that Fe2 dimers opened up a new reaction pathway by promoting the direct breaking of O=O bonds, thus avoiding the usual formation of *OOH intermediates, which helped explain the lower H2 O2 yield and higher specific activity. Abstract : Two is better than one : Fe2 dimers are synthesized through precisely regulating the metal loading on metal–organic frameworks, showing distinct electrocatalytic performance on the reduction of non‐polar diatomic molecules compared with that of single‐atom counterparts. Theoretical calculations show that the structure of Fe2 dimers can promote the fracture of diatomic molecules, so as to avoid side reactions.